Analisis Kompetensi Calon Guru Ekonomi Di Era Revolusi Industri - Neneng Ayu Komala Formi; Yulhendri Yulhendri (Universitas Negeri Padang, 2021)
This study aims to analyze effective learning methods and priorities in the world of education which are based on the competencies that must be possessed by prospective economics teachers in the Economics Education Department, Faculty of Economics, Padang State University in the Industrial Revolution Era. The object of this research is students of the 2016 and 2017 classes of Economic Education, Faculty of Economics, Padang State University. This research uses Analytic Hierarchy Process (AHP) and Expert Choice Software to see the relationship between the competence of prospective teachers in the Industrial Revolution Era as seen from the learning methods collected through questionnaires and documentation. This study uses sampling through Snowball Sampling. The results of this study indicate that 1) the results of the respondents' experiences indicate that creativity is a priority competency for prospective economics teachers in the Industrial Revolution Era. Where creativity is the ability of a prospective teacher to create discoveries regarding learning methods. 2) After researching appropriate learning methods to improve 4Cs, each competency has different results of learning methods in achieving it. In critical thinking and creativity competencies, the method that supports its achievement is hybrid, where hybrid is a learning method that combines traditional face-to-face learning with web-based online learning or learning using computers or others. In addition to improving learning outcomes, hybrid-based learning also improves communication relationships. This hybrid is a supporter of the development of critical thinking competencies and creativity, where when studying online, prospective teachers are asked to be more creative in learning so that students can think critically at the same time. Besides, when learning traditionally is face-to-face, prospective teachers are required to think more critically to make the teaching and learning process between teachers and students more creative.Keywords : 4cs, comptences, methods, ahp, expert choice